Fish Marketing Strategy in Attracting Consumers from a Sharia Economic Law Perspective - Ardinata, Eva Sri Meilani; Hasriadi (Education and Talent Development Center Indonesia (ETDC Indonesia), 2023)
This research is about fish marketing strategies for attracting consumers from a sharia economic law perspective in Sengkang Mini Market, Wajo District. This research is motivated by the strategies of fish sellers who use various methods to gain profits; some of these strategies are not in accordance with sharia economic principles. The objectives of this research are: 1) To determine the market conditions faced by fish sellers at the Sengkang Mini Market. 2) To find out the marketing strategies used by sellers at Sengkang Mini Market. 3) To find out an overview of sharia economic law regarding the marketing strategies carried out by fish sellers at the Sengkang Mini Market. In this research, researchers used qualitative research with normative, sociological, and psychological approaches. Data collection techniques were carried out by means of observation, interviews, and documentation. Data analysis techniques are carried out in three stages: data reduction, data presentation, verification, and conclusions. The results of the research show that the market conditions faced by fish sellers at the Mini Sengkang market experienced a decline in income after the market renovation last year, and fish sellers often did not make a profit in a day. The marketing strategy used by fish sellers at the Sengkang Mini Market to gain profits is by using a marketing mix, namely: product, price, location, and promotion. From the review of sharia economic law, the marketing strategies carried out by fish sellers at the Sengkang Mini Market are partly in accordance with sharia economic principles.